Tradisi gelar songo dan representasi identitas budaya Masyarakat Desa Glagah dalam perspektif Edward Said - Syavira Dwi Kumala Putri (Departemen Pendidikan Sosiologi FISHIPOL UNY, 2024)
This research examines the efforts of the Glagah Village community in preserving the Gelar Songo Tradition amidst the tide of modernization. This phenomenon is important to study considering the challenges faced by traditional communities in maintaining their cultural identity. This research uses a descriptive qualitative approach involving in-depth interviews, participatory observation, and document analysis. This research also aims to analyze the cultural preservation strategies of the Gelar Songo Tradition and assess the impact of community involvement in cultural preservation efforts in this rapidly changing modern era. The research results show that the people of Glagah Village strive to preserve their cultural essence by integrating local values and traditions into the modern context. In this case, Edward Said's theory on the construction of cultural identity becomes relevant, as it emphasizes that identity is not a static entity, but rather the result of continuous negotiation in the face of social change.